EFFICACY OF AZADIRACHTA INDICA AND CAPSICUM ANNUUM POWDERS IN THE PROTECTION OF CEREAL SEEDS AGAINST HARVESTER ANTS MESSOR (HYMENOPTERA: FORMICIDAE) IN MUBI, NIGERIA - Wahedi, Jasini; Oaya, Clement; Elkanah, Obadiah; Ishuwa, Miriam (FUDMA JOURNAL OF SCIENCES, 2021)
Harvester ants (Messor) have become a major pest to farmers because they swarm in to houses, farms and injure seeds, seedlings, and fruits, causing great damage to plants that falls within their vicinity. This study compared the efficacy of Azadirachta indica (neem) and Capsicum annuum (chili pepper) powder for the protection of sorghum and millet grains against harvester ants (Messor) at graded levels. Four ants hills (A, B, C, and D) were identified around Adamawa State University Campus.1.0g, 2.0g and 3.0g of each of the treatment including the positive control (Rambo) was constituted in each ant hill on a petri dish and 100 seeds each for the 2 grains were added. A control (untreated) experiment was set up in every ant hill which contains 100 seeds for every grain but no treatment was added. The results revealed the efficacy of the treatments when compared will the untreated control, but Capsicum annuum performed significantly better. Millet grains were also preferred by the ants, as they recorded the highest number of picking. Therefore, a sustainable used of these plant products in the protection of grains in the field from harvester ants is encouraged in order to have a maximum yield.